1990
DOI: 10.1002/bip.360290116
|View full text |Cite
|
Sign up to set email alerts
|

Z‐RNA: The solution NMR structure of r(CGCGCG)

Abstract: Left-handed double-helical Z-RNA has been studied using the ribohexanucleotide pentaphosphate r(CpGpCpGpCpG). One-dimensional and two-dimensional proton nmr experiments were used to probe the structural details of the left-handed helix in concentrated sodium perchlorate solution. In 1M NaClO4 the RNA adopts the normal A-form double helix, and in 6M NaClO4 it is nearly all in the Z form. In 4M NaClO4 it exists as nearly equal parts of A form and Z form. Resonances corresponding to both A and Z form appear in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 48 publications
2
39
0
Order By: Relevance
“…The work of Davis et al, [18] and Popenda et al, [19] on the high salt structure of a left-handed RNA double helix is well-known. It was found that for the natural ribohexanucleotide r(C P G P C P G P C P G) at 1M concentration a duplex is formed with an A-conformation.…”
Section: Comparison With a Self-complementary Natural Rna And Its 2ꞌ-mentioning
confidence: 99%
“…The work of Davis et al, [18] and Popenda et al, [19] on the high salt structure of a left-handed RNA double helix is well-known. It was found that for the natural ribohexanucleotide r(C P G P C P G P C P G) at 1M concentration a duplex is formed with an A-conformation.…”
Section: Comparison With a Self-complementary Natural Rna And Its 2ꞌ-mentioning
confidence: 99%
“…The crystal structures of nucleosides and nucleotides 23 and solution phase NMR studies [24][25][26][27][28][29] suggest that the conformation of the sugar ring can be adequately described by two conformations such as the C3′-endo-C2′-exo (North sugar) and C2′-endo- Values are for radicals formed via photoexcitation at 143 K in the frozen aqueous (7.5 M LiCl D2O) glassy solution with native pH (ca. 5).…”
Section: Detection Of Sugar Radical Components In Glassy Samples Of Gmentioning
confidence: 99%
“…C3'-endo) conformations. Coupling constants listed in Table 2 were used to determine relative populations of S-and N-type sugars from the Hi'-H2' coupling, and the approximate pseudorotation phase angle (P°) from the additional H2'-H3' and H3'-H4' couplings (23,32).…”
Section: Rna Synthesismentioning
confidence: 99%